2005
DOI: 10.1063/1.2081132
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation in InAs∕InGaAs quantum dots investigated by photoluminescence and capacitance-voltage profiling

Abstract: We present detailed studies of the onset of strain relaxation in InAs/ InGaAs quantum dots. We show that the ground-state photoluminescence ͑PL͒ emission redshifts with increasing the InAs coverage before relaxation and blueshifts when relaxation occurs. PL spectra of the relaxed samples show two predominant families of dots with very different temperature-dependent efficiency. By comparison we show that the dots emitting at long wavelength are degraded by relaxation while the dots emitting at short wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The FWHM increase is related to the presence of two peaks with lower (0.941 eV) and higher (0.957 eV) energies than for the sample with 5 nm thick cap layer (0.947 eV). An emission energy blue-shift resulting from strain relaxation has been already reported when the InAs coverage is increased beyond a critical thickness [11]. So, relaxed QDs are probably responsible of the stronger peak at 0.957 eV but the presence of the low energy peak also shows that the relaxation is not uniform.…”
Section: Introductionmentioning
confidence: 90%
“…The FWHM increase is related to the presence of two peaks with lower (0.941 eV) and higher (0.957 eV) energies than for the sample with 5 nm thick cap layer (0.947 eV). An emission energy blue-shift resulting from strain relaxation has been already reported when the InAs coverage is increased beyond a critical thickness [11]. So, relaxed QDs are probably responsible of the stronger peak at 0.957 eV but the presence of the low energy peak also shows that the relaxation is not uniform.…”
Section: Introductionmentioning
confidence: 90%
“…1-16͒ is necessary for designing QD devices. 19 This blueshift contradicts an effect of compressive strain reduction in the QDs, which is expected to produce a redshift. Growing an InGaAs capping layer on top of the QDs leads to strain relaxation by the generation of the lattice misfits in the bottom GaAs layer near the QDs while the top GaAs layer is dislocation-free.…”
mentioning
confidence: 95%
“…As a rule, the best optical quality of QDs is attained at a small excess of d eff over d *: d eff ~ (1.1-1.2) d *, although the quantity d * as such may vary within a rather wide range from 1.7 to 4 monolayers, depending on the substrate temperature, the relationship between the fluxes of reagents, and the particular type of the heteropair. The process of growth of QDs in InAs/GaAs heterostructures with the increased thickness d eff was studied elsewhere [1][2][3][4][5]. It was shown that, with increasing d eff , the dispersion of QDs in size and the number of relaxed large-sized defect InAs clusters increase along with the density of QDs.…”
Section: Introductionmentioning
confidence: 99%